Avaliação do uso de agentes desidratantes e catalisadores metálicos impregnados em diferentes suportes na síntese direta de dimetilcarbonato - Faria, Douglas José (2022)
CO2 chemical transformation is an exciting way to reduce this gas concentration in the atmosphere. CO2 is used to produce dimethylcarbonate (DMC) via direct synthesis, a promising route from the environmental perspective. However, direct synthesis has unfavorable thermodynamics and catalytic deactivation due to water formation. This problem motivated us to investigate the dehydration effect on the DMC direct synthesis. Here, different dehydrating agents (2,2-dimethoxypropane, sodium sulfate, magnesium oxide and butylene oxide) were combined with molecular sieves to remove water and minimize the reverse reaction, in addition to the analysis of the use of catalysts impregnated in activated carbon, silica, alumina and eggshell. A new reactor with compartment to accommodate molecular sieves in the gas phase was also developed. The catalysts were synthesized by the impregnation method and characterized by TGA, SEM-FEG, BET, TPD-NH3, EDS, mapping, FTIR-UATR and XRD. Chemical analysis of the products was performed by gas chromatography. The optimization of the amount of catalyst, pressure, temperature and recyclability of the best catalyst under optimized conditions and in the presence of different dehydrating agents were also carried out. For the synthesis of DMC, the highest conversion of methanol was for molecular sieves in the gas phase with 2,2-dimethoxypropane in the liquid phase and potassium methoxide as catalyst (conversion = 48.6%; selectivity of 88%), still, the analysis of the impregnated catalysts showed that AC-Fe is the most efficient in the synthesis of DMC, with a conversion of 23.5% and a selectivity of 100% (80 °C, 40 bar and 24h). Reaction optimization (120 °C, 40 bar and 24h) using AC-Fe resulted in a DMC yield of ~30%. The recycling of the catalytic systems proved that the combination of molecular sieve and AC-Fe can maintain the selectivity at 100%, slightly decreasing the yield.